The Aesthetics of Malemang Dance in Tanjung Pisau Village, Bintan District, Riau Islands Province - Puja Asrita; Darmawati (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to find, describe and analyze the aesthetics of Malemang dance in Tanjung Pisau Village, Bintan Regency, Riau Islands Province. The type of research used is qualitative. The research instrument is the researcher himself by using tools such as stationery and recording devices. To obtain data, it is done through literature study, observation, interviews, and documentation. The object of research is Malemang dance. The steps of data analysis were carried out by data reduction, data presentation, and conclusion drawing. Based on the results of the study, it can be concluded that Malemang dance has beauty, characteristics and uniqueness in terms of motion and performance. The beauty can be seen from the form or shape and arrangement of the main elements of motion, which consists of motion names and motion descriptions. As for the form of supporting elements, namely the formation of a straight line dancer floor design and forming a circle formation. The musical instruments used are gong, violin, and drum. The makeup used in this performance is beautiful makeup and wears a Malay kurung shirt costume. The weight in this Malemang dance is that the meaning can be felt from the atmosphere, ideas, or ideas, as well as the meaning or message contained in the Malemang dance. the appearance in Malemang dance can be appreciated in terms of talent and skill.